2020
DOI: 10.1038/s41467-020-18284-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulating electrolyte structure for ultralow temperature aqueous zinc batteries

Abstract: Rechargeable aqueous batteries are an up-and-coming system for potential large-scale energy storage due to their high safety and low cost. However, the freeze of aqueous electrolyte limits the low-temperature operation of such batteries. Here, we report the breakage of original hydrogen-bond network in ZnCl2 solution by modulating electrolyte structure, and thus suppressing the freeze of water and depressing the solid-liquid transition temperature of the aqueous electrolyte from 0 to –114 °C. This ZnCl2-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
524
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 543 publications
(603 citation statements)
references
References 70 publications
(84 reference statements)
14
524
1
Order By: Relevance
“…This value is relatively similar to that for ZnSO 4 powder of ≈1092.4 cm −1 and therefore confirms the modified Zn 2+ solvation sheath. The weakened Zn 2+ solvation affects the transference number ( t Zn2+ ) in the electrolyte of Anti‐M‐50 % [26] . As shown in Figure S5, t Zn2+ was computed to be 0.48, higher than that for aqueous ZnSO 4 electrolyte (0.34), [5, 7a] which suggests a faster migration speed of Zn 2+ in Anti‐M‐50 %.…”
Section: Resultsmentioning
confidence: 93%
“…This value is relatively similar to that for ZnSO 4 powder of ≈1092.4 cm −1 and therefore confirms the modified Zn 2+ solvation sheath. The weakened Zn 2+ solvation affects the transference number ( t Zn2+ ) in the electrolyte of Anti‐M‐50 % [26] . As shown in Figure S5, t Zn2+ was computed to be 0.48, higher than that for aqueous ZnSO 4 electrolyte (0.34), [5, 7a] which suggests a faster migration speed of Zn 2+ in Anti‐M‐50 %.…”
Section: Resultsmentioning
confidence: 93%
“…Chen et al. reported the breakage of hydrogen bonding networks in concentrated ZnCl 2 electrolytes (Figure 2d) [57] . As shown in Figure 2e, the freezing point can be decreased to −114 °C by modulating the concentration of electrolytes.…”
Section: Design Of Anti‐freezing Electrolytesmentioning
confidence: 85%
“…Chen et al reported the breakage of hydrogen bonding networks in concentrated ZnCl 2 electrolytes ( Figure 2d). [57] As shown in Figure 2e, the freezing point can be decreased to À 114°C by modulating the concentration of electrolytes. The Zn-polyaniline (PANI) battery using this electrolyte can work at a wide temperature range from -90 to 60°C, better than the common electrolytes (Figure 2fÀ h).…”
Section: àmentioning
confidence: 93%
See 2 more Smart Citations